2014
DOI: 10.33549/physiolres.932761
|View full text |Cite
|
Sign up to set email alerts
|

D-Galactosamine/Lipopolysaccharide-Induced Hepatotoxicity Downregulates Sirtuin 1 in Rat Liver: Role of Sirtuin 1 Modulation in Hepatoprotection

Abstract: D-Galactosamine/Lipopolysaccharide (D-GalN/LPS) is a well known model of hepatotoxicity that closely resembles acute liver failure (ALF) seen clinically. The role of sirtuin 1 in this model has not yet been documented. However, there have been a number of studies about the cytoprotective effects of resveratrol, a SIRT1 activator, in the liver. This study was aimed at elucidating the roles of SIRT1 protein expression or catalytic activity in D-GalN/LPS model of hepatotoxicity. ALF was induced in male Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…Administering D-GaIN generated free radicals that stimulated LPO. D-GalN in combination with lipopolysaccharide treatment induces hepatotoxicity and significantly increase all markers of liver injury and LPO (39). Several researchers have suggested that various compounds, such as flavonoids, lycopene, and magniferin, ameliorate D-GaIN-induced acute liver injury due to their antioxidant activities (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Administering D-GaIN generated free radicals that stimulated LPO. D-GalN in combination with lipopolysaccharide treatment induces hepatotoxicity and significantly increase all markers of liver injury and LPO (39). Several researchers have suggested that various compounds, such as flavonoids, lycopene, and magniferin, ameliorate D-GaIN-induced acute liver injury due to their antioxidant activities (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The liver injury induced by LPS/GalN in mice is a classical model widely used in experimental investigation of fulminant hepatitis. 27 The exposure to LPS/GalN stimulates a strong inflammatory response in the liver, and the liver injury largely depends on the excessive induction of the detrimental inflammatory mediators such as TNF-α. 28 The anti-inflammatory actions of ACEI have been well studied both in vitro and in vitro previously.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of 10 µg/kg LPS with 400 mg/kg D-GalN produced a nonlethal hepatitis as proved histologically and biochemically evidenced by increases in ALT, AST, alpha-GST, NO, and the mRNA levels of the studied genes (Farghali et al 2009). Therefore, D-GalN/LPS combinations with different amounts of D-GalN/LPS appear very well reproducible model for in vivo experimental hepatitis studies , Kemelo et al 2014, Kemelo et al 2016. Moreover, a single dose of acetaminophen (APAP, 1 g/kg) was applied to rat to produce mild degree of hepatotoxicity (Wojnarova et al 2015).…”
Section: D-galactosamine/lipopolysaccharide-induced Fulminant Liver Failure and Acetaminopheninduced Liver Injurymentioning
confidence: 96%
“…The studies of Kemelo (Kemelo et al 2014, Kemelo et al 2016) reported that D-GalN/LPS-induced hepatotoxicity downregulates SIRT1 in rat liver and discussed the role of sirtuin 1 modulation in hepatoprotection. The role of sirtuin 1 in this model has not been documented before.…”
Section: Resveratrol and Related Compounds As Antioxidants In D-galn/lps-induced Hepatoxicity: Role Of Sirtuin 1 Modulation In Hepatoprotmentioning
confidence: 99%